If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(y + -6) = y + 3 + 2y Reorder the terms: -2(-6 + y) = y + 3 + 2y (-6 * -2 + y * -2) = y + 3 + 2y (12 + -2y) = y + 3 + 2y Reorder the terms: 12 + -2y = 3 + y + 2y Combine like terms: y + 2y = 3y 12 + -2y = 3 + 3y Solving 12 + -2y = 3 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 12 + -2y + -3y = 3 + 3y + -3y Combine like terms: -2y + -3y = -5y 12 + -5y = 3 + 3y + -3y Combine like terms: 3y + -3y = 0 12 + -5y = 3 + 0 12 + -5y = 3 Add '-12' to each side of the equation. 12 + -12 + -5y = 3 + -12 Combine like terms: 12 + -12 = 0 0 + -5y = 3 + -12 -5y = 3 + -12 Combine like terms: 3 + -12 = -9 -5y = -9 Divide each side by '-5'. y = 1.8 Simplifying y = 1.8
| 4x-5/3-7x=4 | | -9=-177n | | Y^3=9 | | n+4-9-5=0 | | -3x+7=5-(8x+4) | | t=225+0.02(325) | | 19n+17=14n-13 | | 3x+62=3x-9 | | t=200+25+.02x | | 5-(6-(3-(7+3)))= | | 4.2+3.9+5+x=21.5 | | X+11=3x+62 | | 25+8k=3(8+3k)-7 | | 5x-13=-27 | | x+11=3x-9 | | -11r-12r=0 | | (4z/11)+(3/11)=-1 | | 8(4x-2)=4(8x+8) | | 33-4(5)+6= | | (4a/5)-(7/5)=(-3/5) | | 8/9+9/-4 | | 2x^2-6x=-5 | | 6x-10=11x-20 | | 1+2b-3b=-4 | | 1c-45=4c+3 | | 33-4n+6forn=5 | | -1/6(x-12)+1/3(x+3)=x-27 | | 8(t+2)-3(t-4)=-3(5y-7)+8 | | 9+11x-7=9x+18-2x | | -2(p-5)+5p=-5 | | 4X+32Y=-16 | | 4+12a=22+6a |